Analysis of Farmers' Independence Strategies in Land Conservation and the Implementation of Flood Management Models in Pandeglang Regency - solihin, Ihin; Handoko, Pryo; Hendrarso, Panji (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to develop exit protocols that promote the autonomy of conservation farmers by applying a Flood Management model in specific river basins within Pandeglang Regency. The present work utilizes the C.I.P.P. (Context, Input, Process, Product) and U.S.G. (Urgency, Seriousness, Growth) methodologies to assess the long-term viability of land conservation initiatives executed by farmers. Contextual input, process, and outcome analysis of implementing the flood management model is conducted using C.I.P.P. At the same time, the Urgency, Severity of the challenges, and prospective growth resulting from this program are assessed using U.S.G. A study revealed that when applied in specific river basin regions, the flooding management program can improve farmers' capacity to adapt and mitigate against flood hazards. Successful application of community-based conservation measures has demonstrated favourable outcomes in land administration and the improvement of food security. However, the long-term viability of the initiative relies on an exit strategy that ensures farmers' autonomy without necessitating external support. This approach entails enhancing the capabilities of farmers, broadening their sources of income, and enhancing their ability to reach markets and employ technology. The findings of this study will likely function as valuable policy suggestions to improve the sustainability of land protection and flood management within the Pandeglang Regency.